Anaemia of Pregnancy, Perinatal Outcomes and Children's Developmental Vulnerability: a Whole‐of‐Population Study. Issue 5 (September 2014) - Smithers, Lisa G.; Gialamas, Angela; Scheil, Wendy; Brinkman, Sally; Lynch, John W.
Abstract Background There is limited longitudinal data from high‐income countries on the sequelae of anaemia during pregnancy. The aim of this study is to examine whether anaemia of pregnancy is associated with adverse perinatal outcomes and with children's developmental vulnerability. Methods We conducted a population‐based study to link routinely collected government administrative data that involved all live births in the state of South Australia 1999–2005 (n = 124 061) and a subset for whom developmental data were collected during a national census of children attending their first year of school in 2009 (n = 13 654). Perinatal outcomes were recorded by midwives using a validated, standardised form. Development was recorded by schoolteachers using the Australian Early Development Index (AEDI). Children in the lowest 10% of AEDI scores are indicative of developmental vulnerability. Results There were 8764/124 061 (7.1%) cases of anaemia. After adjustment for a range of potentially confounding factors, anaemia of pregnancy was associated with a higher risk of fetal distress [incident rate ratio (IRR) 1.20 [95% CI 1.13, 1.27]] and preterm birth <37 weeks gestation (IRR 1.23 [1.15, 1.31]), slightly higher birthweight [14 g (2, 26)] and newborns were less likely to require resuscitation (IRR 0.94 [0.91, 0.097]). Anaemia of pregnancy was not associated with children's developmental vulnerability after adjustment for maternal, obstetric and sociodemographic covariables, either in complete case analyses (n = 11 949) or after imputation for missing data (n = 13 654). Conclusions Anaemia of pregnancy is associated with perinatal complications but not with children's developmental vulnerability at school entry.